The Future Of Medical Work in Southern Africa : Case Study of the Future of Medical Work and the Impact of the COVID-19 Pandemic on Medical Work in South Africa - Ivins, Courtney Price; Annie Liang; Serfontein, Nicole Danielle; Schneider, Pia Helene; Matsebula, Thulani Clement (Washington, DC: World Bank, 2022)
Major global trends such as economic integration, urbanization, climate change, demographic shifts, digital and technological advances, and rising consumerism will all affect population health and shape the future of medical work. In South Africa, these trends can be harnessed as opportunities, but this will require the government to take a strategic approach and to give its immediate attention to six health workforce issues: (i) the mismatch between the number and the skills of health graduates produced by the health education system and the number and specialties needed for future medical work; (ii) the unsustainable financing system for expensive medical education; (iii) the large numbers of foreign-trained medical graduates whose degrees are not being fully recognized in South Africa; (iv) high vacancy rates in health facilities coinciding with high unemployment and inadequate human resource management; (v) insufficient data on the health workforce; and (vi) the public sector’s reluctance to collaborate with the private sector and international health labor. With more large-scale disasters looming, South Africa’s experience with the COVID-19 pandemic will provide important lessons for the future of medical work. Based on the findings of this case study, we make recommendations on health education policy and human resource policy. These include (i) investing in high- quality education and aligning investments in health education and medical research with future needs; (ii) looking for innovative ways to finance medical education; (iii) investing in the health workforce on the basis of health workforce planning and future projections of need; (iv) modernizing the human resource management in health facilities and facilitating the use of modern technology; (v) making substantial investments in the collection and analysis of data on the health workforce and using results in workforce planning; and (vi) expanding public-private sector collaboration and developing policies to manage the mobility of the health workforce to and from the private sector and abroad.